The Hitchcock Hotel [large type] - Wrobel, Stephanie (Thorndike Press, a part of Gale, a Cengage Company, 2024)
"Alfred Smettle is not your average Hitchcock fan. He is the founder, owner, and manager of The Hitchcock Hotel, a sprawling Victorian house in the White Mountains dedicated to the Master of Suspense. There, Alfred offers guests round-the-clock film screenings, movie props and memorabilia in every room, plus an aviary with fifty crows. To celebrate the hotel's first anniversary, he invites his former best friends from his college Film Club for a reunion. He hasn't spoken to any of them in sixteen years, not after what happened. But who better than them to appreciate Alfred's creation? And to help him finish it. After all, no Hitchcock set is complete without a body."--